Value co-creation in business-to-business context: A bibliometric analysis using HistCite and VOS viewer - Ullah, Fawad; Shen, Lei; Shah, Syed Hamad Hassan (Frontiers in Psychology, 2023)
Value Co-creation (VCC) recently showcased a significant increase in publication frequency in business studies and social sciences. Our study objects to study the current status of VCC in B2B principally in the field of marketing by systematically extracting the research articles published in last 2 decades through Web of Science (WoS). We took the services of HistCite to determine the dynamics of VCC research and then conduct Bibliographic coupling and Cartographic analysis using VoS Viewer. We explored the most co-occurred keywords, we also found out that Finland showed the highest number of publication. Furthermore Vargo and lusch was the most influential authors and Industrial marketing management was the journal with most publications. Additionally Business and Economics were the hot and critical research areas while Lappeeranta University and Alto University were the countries with the most publications. Three research streams have emerged during cluster analysis that indicate the prominent role of VCC in B2B Context. (1) VCC in B2B, (2) VCC and organizational capabilities and (3) VCC in buyers and sellers interface. Our research provided a base for conceptualizing VCC publications related to Business, Management and Economics in B2B context. Content analysis reveal that the research on VCC in B2B context is in its initial stage and future research might open new research paradigms. While costumers and producers working jointly, organizations can co-create value for their products and services with negligible costs and achieving higher market shares and competitive edge over competitors.